THU0338 Incidence of selected opportunistic infections among children with juvenile idiopathic arthritis. (23rd January 2014) - Beukelman, T.; Xie, F.; Baddley, J.W.; Chen, L.; Delzell, E.; Grijalva, C.; Patkar, N.; Saag, K.G.; Winthrop, K.; Curtis, J.R.
Abstract : Background: There may be an increased risk of opportunistic infections among children with juvenile idiopathic arthritis (JIA), especially with exposure to immunosuppressant medications. No controlled studies to address this question have been published to date. Objectives: We determined incidence rates of selected opportunistic infections among children with and without JIA and examined the effects of immunosuppressant medications. Methods: Using United States national Medicaid administrative claims data from 2000 through 2005, we identified a cohort of children with JIA based on physician diagnosis codes and dispensed medications. We defined a non-JIA comparator cohort of children diagnosed with attention deficit hyperactivity disorder. All subjects had a 3 month baseline period prior to study follow-up to assess for prevalent opportunistic infections (which excluded patients from analysis) and current medication exposures. All medication exposures to methotrexate (MTX), TNF inhibitors, and systemic glucocorticoids (GC) were considered current for 30 days past the days supplied by the last filled prescription. Hospitalized and outpatient incident opportunistic infections were identified using physician diagnosis or hospital discharge codes. Identification of some infections (mycoses, tuberculosis, and herpes zoster) also required evidence of treatment with specific antimicrobial medications within 90 days. We calculated infection incidence rates (IR). The rates in the non-JIA comparator cohort were standardized to the age, sex, and race distribution of the JIA cohort. We calculated incidence rate ratios (IRR) to compare infection rates. Results: The JIA cohort included 8, 503 children with 14, 370 person-years of follow-up; 1, 392 used TNF inhibitors and 3, 491 used MTX during follow-up. The non-JIA comparator cohort included 360, 362 children with 490, 939 person-years of follow-up. When all opportunistic infections were considered together as a single outcome, there were 42 infections in the JIA cohort (IR 300 [216-406] per 100, 000; IRR 2.4 [1.7-3.3] versus non-JIA comparator). Among all children with JIA, there were no identified infections with Aspergillus, Blastomyces, Histoplasma, Cryptococcus, Legionella, Listeria, JC virus, or tuberculosis. We identified 1 infection each (IR 7 per 100, 000) with Nocardia, non-tuberculous mycobacteria, Toxoplasma, and Pneumocystis . We identified 3 infections with Coccidioides (IR 21 per 100, 000; IRR 101 [8.1-5319] versus non-JIA comparator); 5 infections with Salmonella (IR 35 per 100, 000; IRR 3.8 [1.2-9.5]); and 32 cases of herpes zoster (IR 225 per 100, 000; IRR 2.1 [1.4-3.0]). Among children with JIA, herpes zoster was not strongly associated with current use of GC (IRR 1.8 [0.6-4.5] versus no current GC use), MTX (IRR 1.4 [0.5-3.6] versus no current MTX or TNF inhibitor use), or TNF inhibitors (IRR 2.2 [0.7-6.9] versus current MTX use without current TNF inhibitor use). Conclusions: Opportunistic infections are rare among children with JIA. Nevertheless, children with JIA had a higher rate of opportunistic infections, including Coccidioides, Salmonella, and herpes zoster, than children without JIA. Herpes zoster was not strongly associated with specific medications used to treat JIA. Disclosure of Interest: T. Beukelman Grant/Research support from: Pfizer, Consultant for: Novartis, F. Xie: None Declared, J. Baddley Consultant for: Abbot, Merck, L. Chen: None Declared, E. Delzell Grant/Research support from: Amgen, C. Grijalva: None Declared, N. Patkar: None Declared, K. Saag Consultant for: Amgen, AstraZeneca, Lilly, Genentech, Sanofi-Aventis, Merck, Novartis, Savient, Ardea, Regeneron, K. Winthrop Consultant for: Amgen, Pfizer, Abbott, Wyeth, J. Curtis Consultant for: Roche/Genentech, UCB, Centocor, CORRONA, Amgen, Pfizer, BMS, Crescendo, Abbot